Pengaruh Keharmonisan Keluarga Terhadap Kenakalan Remaja - Ansyari, Shifa Maisya; Amirah, Siti Atha; Aqlira, Sofi Dwi; Prasojo, Tanzandiro Maulana (Universitas Pakuan, 2025)
The Influence of Family Harmony on Juvenile DelinquencyThis study aims to analyze in depth the influence of family harmony on juvenile delinquency among students at SMA Unggulan Al-Azhar Medan. The background of this research arises from the growing phenomenon of adolescent behavioral deviations such as fighting, truancy, bullying, and other forms of misconduct, which are strongly suspected to be linked to poor emotional relationships within families. The family serves as the primary foundation in shaping adolescents’ personality, moral values, and character. Harmonious families characterized by open communication, affection, and active involvement play a crucial role in preventing negative behaviors. This study employed a qualitative research approach using a Google Form questionnaire distributed online to gather data from students. The results reveal that most respondents come from fairly harmonious families, reflected in healthy communication patterns, mutual appreciation, and sufficient emotional support. These conditions correlate with a relatively low level of juvenile delinquency at the school. Nevertheless, some cases of deviant behavior were identified, commonly resulting from lack of parental attention, internal family conflict, and negative social environmental influences. The findings indicate that the higher the level of family harmony, the lower the risk of juvenile delinquency. Therefore, continuous efforts to strengthen family communication, empathy, and emotional closeness are essential preventive strategies for promoting positive adolescent development and reducing behavioral problems.